2011
DOI: 10.1055/s-0031-1279995
|View full text |Cite
|
Sign up to set email alerts
|

Glycosides from the Methanol Extract ofNotopterygium incisum

Abstract: Five new (1-5) and twelve known (6-17) different types of glycosides together with a known sesquiterpene triol (18) were isolated from the methanol extract of the rhizomes of Notopterygium incisum. The new structures were elucidated by means of spectroscopic and chemical methods to be pregn-5-en-3 β,20( S)-diol-3- O-bis-β-D-glucopyranosyl-(l → 2,1 → 6)-β-D-glucopyranoside (1), oleuropeic aldehyde 8-O-β-D-glucopyranoside (2), 2( R)-(3,4-dimethoxyphenyl)-propane-1,3-diol-1-O- β-D-glucopyranoside (3), eudesman-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Ananthi et al [13] have elucidated the effective biological constituents from marine plants by polar solvent for the treatment of lipidized brain related diseases and disorders. The methanolic extracts were used to fractionate the active glycosidic constituents of T. ornata and evaluated for their biological activities [23].…”
Section: Discussionmentioning
confidence: 99%
“…Ananthi et al [13] have elucidated the effective biological constituents from marine plants by polar solvent for the treatment of lipidized brain related diseases and disorders. The methanolic extracts were used to fractionate the active glycosidic constituents of T. ornata and evaluated for their biological activities [23].…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical studies have shown that coumarins, phenoloids, flavonoids and their glycosides, and essential oils are the main types of chemicals in NF [5,6,7]. Among these, coumarins, especially isoimperatorin, notopterol, and bergapten, are well known to be the major bioactive compounds, and contribute to NF’s anti-inflammatory, analgesic, and anti-cancer activities [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical investigations revealed that the rhizomes of N . incisum contained phenolic compounds, alkaloids, polyacetylenes, coumarins, sesquiterpenoids, and glycosides [21,22,23,24,25,26,27,28,29,30,31,32,33,34]. Pharmacological studies have revealed that its extracts or constituents possess anti-inflammatory, antioxidative, analgesic, and anti-influenza activity as well as antiproliferative activity against several cancer cell lines [21,22].…”
Section: Introductionmentioning
confidence: 99%